Effects of smoking cessation on individuals with COPD: a systematic review and meta-analysis - Zihan Wang; Zihan Wang; Yifan Qiu; Xiang Ji; Liang Dong; Liang Dong (Frontiers in Public Health)
ObjectiveDespite smoking being a significant risk factor in the occurrence and progression of chronic obstructive pulmonary disease (COPD), no comprehensive analysis has been conducted to determine the potential benefits of smoking cessation for patients with established COPD or identify specific indicators that may be improved. The aim of our meta-analysis was to elucidate the positive impact of smoking cessation on COPD.MethodsWe conducted a comprehensive search of PubMed, EMBASE, Web of Science, Cochrane Library, CNKI, Wan Fang and VIP databases to identify studies that met our eligibility criteria from inception up to 1, May 2024. Data were extracted independently by two authors and pooled using a random-effects model. Study quality was evaluated using the Newcastle-Ottawa Scale (NOS).ResultsPreliminary screening of publications gave a total of 13,460 documents after which the repetitive and non-compliant studies were removed. Eventually, 11 studies were included for follow-up analysis. The pooled results showed that cessation of smoking produced significant improvements in forced expiratory volume in one second (FEV1)% predicted (MD = 6.72, 95% CI, 4.55–8.89, P < 0.001; I2 = 53%), FEV1/forced vital capacity (FVC) (MD = 6.82, 95% CI, 5.09-8.54, P < 0.001; I2 = 0%), modified Medical Research Council (mMRC) (MD = −0.49, 95% CI, −0.95–−0.02, P = 0.040; I2 = 73%), 6-minute walk test (6-MWT) (MD = 64.46, 95% CI 14.60-114.32, P = 0.010; I2 = 94%), partial oxygen pressure (MD = 1.96, 95% CI, 1.03-2.89, P < 0.001; I2 = 0%), mortality (RR = 0.75, 95% CI, 0.56-1.00, P = 0.05; I2 = 44%).ConclusionOur meta-analysis presented suggestive evidence that smoking cessation offered significant benefits to COPD patients, notably in the improvement of specific key indicators of pulmonary function (FEV1% predicted, FEV1/FVC), alleviating symptoms, enhancing exercise tolerance, and could reduce mortality.PROSPERO registrationhttps://www.crd.york.ac.uk/prospero/, identifier: CRD42022384123.